Making Sense of Homeschooling Approaches Through Content Analysis - Lai, Andrea (Alberta Journal of Educational Research, 2023)
A common problem for new homeschoolers is understanding how to choose and implement specific educational approaches. In response, I conducted a qualitative content analysis on key texts representative of popular homeschooling approaches, including The Well-Trained Mind (classical), Home Education (Charlotte Mason), and Teach Your Own (unschooling); and compared these to current classroom-based learning. This paper finds that classical homeschooling and modern-day classroom teaching are similar; the Charlotte Mason approach is the most varied in teaching methods; and unschooling makes little mention of teaching methods. This report also suggests that homeschooling families can be defined by the teaching methods they regularly employ. Keywords: homeschooling, teaching method, classical, Charlotte Mason, unschooling Un problème courant pour les nouveaux enseignants à domicile est de comprendre comment choisir et mettre en œuvre des approches éducatives spécifiques. J'ai donc procédé à une analyse qualitative du contenu de textes clés représentatifs des approches populaires de l'enseignement à domicile, notamment The Well-Trained Mind (classique), Home Education (Charlotte Mason) et Teach Your Own (non-scolarisation), et je les ai comparés à l'apprentissage actuel en classe. Cet article constate que l'enseignement classique à domicile et l'enseignement moderne en classe sont similaires, que l'approche de Charlotte Mason est la plus variée en termes de méthodes d'enseignement et que l'approche de non-scolarisation ne mentionne guère les méthodes d'enseignement. Cet article suggère également que les familles qui font l'école à la maison peuvent être définies par les méthodes d'enseignement qu'elles emploient régulièrement. Mots clés : enseignement à domicile, méthode d'enseignement, classique, Charlotte Mason, non‑scolarisation